In vitro effect of clarithromycin and alginate lyase against helicobacter pylori biofilm. (8th September 2016) - Bugli, F.; Palmieri, V.; Torelli, R.; Papi, M.; De Spirito, M.; Cacaci, M.; Galgano, S.; Masucci, L.; Paroni Sterbini, F.; Vella, A.; Graffeo, R.; Posteraro, B.; et al.
Abstract : It is now established that the gastric pathogen Helicobacter pylori has the ability to form biofilms in vitro as well as on the human gastric mucosa. The aim of this study is to evaluate the antimicrobial effects of Clarithromycin on H. pylori biofilm and to enhance the effects of this antibiotic by combining it with Alginate Lyase, an enzyme degrading the polysaccharides present in the extracellular polymeric matrix forming the biofilm. We evaluated the Clarithromycin minimum inhibition concentration (MIC) on in vitro preformed biofilm of a H. pylori . Then the synergic effect of Clarithromycin and Alginate Lyase treatment has been quantified by using the Fractional Inhibitory Concentration index, measured by checkerboard microdilution assay. To clarify the mechanisms behind the effectiveness of this antibiofilm therapeutic combination, we used Atomic Force Microscopy to analyze modifications of bacterial morphology, percentage of bacillary or coccoid shaped bacteria cells and to quantify biofilm properties. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 32:1584–1591, 2016